Community health workers: A key to halting Africa’s mpox outbreak - Ngashi Ngongo; Yap Boum II; Kyeng Mercy; Landry D. Tsague; Wazih N. Cho; Gervais L. Folefack Tengomo; Abou Beckr Gaye; Laura N. Ambe; Nebiyu Dereje; Jean Kaseya (Journal of Public Health in Africa)
No abstract available.